Mechanistic Insight into the 1,3,2-Diazaphospholene-Catalyzed Reductant (HBpin/NH3BH3)‑Controlled Reaction of Allyl 2‑Phenylacrylate: Claisen Rearrangement or Hydrogenation? - Yang, Linlin; Zhang, Shuoqi; Zeng, Guixiang (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2021)
Mechanistic study on the 1,3,2-diazaphospholene (1)-catalyzed reduction reaction of allyl 2-phenylacrylate 4 with HBpin or ammonia borane (AB) was systematically performed by the density functional theory (DFT) method. When HBpin is employed as the reductant, the reductive Ireland–Claisen (IC) rearrangement reaction occurs. First, the active species P-hydrido-1,3,2-diazaphospholene 3 is generated through the metathesis reaction of 1 with HBpin. Next, the terminal CC double bond of 4 is inserted into the P–H bond of 3 to produce 6a through the 1,2-addition (Markovnikov) step, which is followed by the pinB–H bond activation to afford key boron enolate 8. Then, 8 undergoes the [3,3] rearrangement that is followed by the alcoholysis reaction with methanol leading to the final product γ,δ-unsaturated carboxylic acid. The [3,3] rearrangement step is the rate-determining step with the Gibbs energy barrier (ΔG ≠) and Gibbs reaction energy (ΔG) of 23.9 and −27.5 kcal/mol, respectively. When AB is employed as the reductant, the transfer hydrogenation reaction occurs through two comparable pathways, 1,2- and 1,4-transfer hydrogenation pathways. The former pathway directly leads to the hydrogenation product with the ΔG ≠ and ΔG values of 22.4 and −27.7 kcal/mol, respectively. The latter pathway produces an enolate intermediate (rate-determining step, ΔG ≠/ΔG = 24.1/–0.3 kcal/mol) first, which then prefers to undergo the enol–keto tautomerism instead of the [3,3] rearrangement to afford the hydrogenation product. Obviously, the generation of the boron enolate plays a crucial role in the reductive IC rearrangement reaction because it prevents the enol–keto tautomerism.